U-2: THE NEED FOR JURISPRUDENCE AND JURISPRUDENCE IN CONTEMPORARY TIMES AND A RESEARCH REVIEW OF RELIGIOUS JURISPRUDENCE.: عصرِ حاضر میں فقہ واجتہادکی ضرورت اور مذاہبِ فقہیہ کا تحقیقی جائزہ - Noor ul Haq, Mufti; Mumtaz , Engneer Amir; Kahalid, Muhammad Numan (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2022)
No doubt, The Holy Quran and Sunnah give intellgible interpretations of all Islamic rules regarding the necessities of human life and matters which are cemented to him. It is obvious to note that five hundred verses of the Quran and three thousand Sayings of Prophet Muhammad (S.A.W) are connected to elucidate these principles. In pragmatic life, there are a lot of dilemmas that acquire solutions facing people of different brackets of life. Here the question arises, how many millions of issues could be solved i.e apparently impossible for a layman to extract solutions by him through these basic thirty-five hundred principles? In point of fact, it requires Islamic jurisprudence evolved by the pious and dedicated scholars of the past like Imam Abu Hanifa, Imam Malik, Imam Shafai, and Imam Ahmad (R.A). Bear in mind that this Islamic jurisprudence is completely based on the Quran and Sunnah necessarily. Work on Islamic Jurisprudence has been compiled by those great Imams which gives solutions based on Sharia, within two hundred years after the migration of Prophet Muhammad (S.A.W). At the beginning of the third century, people mostly started to follow these four Fiqhs with the exception of Abu Dawood Al-Zahri. In the sixth century, all Muslim Ummah commenced following one of them. In short, all Muslims should be grateful to Allah and the people who dedicated their lives in order to serve Islam in such a mode that is unobjectionable and has provided solutions to all vexed questions.